2016
DOI: 10.1038/srep29513
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants in the Transcriptional Regulatory Region of the ALOX5AP gene and Susceptibility to Ischemic Stroke in Chinese Populations

Abstract: No coding sequence variants of the ALOX5AP gene that lead to amino acid substitutions have been identified. A two-stage study design was used to explore the relationship between variants in the transcriptional regulatory region of ALOX5AP gene and ischemic stroke (IS) risk in Chinese populations. IS was determined using CT and/or MRI. First, 18 SNPs, located in the upstream promoter region of ALOX5AP gene, were genotyped in 200 IS patients and 200 controls. And one potential associated SNP (rs17222919) was ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Our study has only evaluated one of the main SNPs in this region, while other effective SNPs are also present. Although not all of these SNPs were related to ischemic stroke in other populations, 11 however, they could be an effective predictor of stroke in our population and could be the subject of future studies. As a matter of fact, evaluating ALOX5AP polymorphism in different populations seems necessary to establish regional guidelines about genetic risk factors for developing stroke.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Our study has only evaluated one of the main SNPs in this region, while other effective SNPs are also present. Although not all of these SNPs were related to ischemic stroke in other populations, 11 however, they could be an effective predictor of stroke in our population and could be the subject of future studies. As a matter of fact, evaluating ALOX5AP polymorphism in different populations seems necessary to establish regional guidelines about genetic risk factors for developing stroke.…”
Section: Discussionmentioning
confidence: 83%
“…Some studies have reported an association between ALOX5AP promoter polymorphism (rs17222919) and stroke. 9 - 11 While stroke is a multifactorial and polygenic disease, studying such polymorphisms along with other traditional risk factors is useful for establishing life style modifications as well as predicting patient’s response to treatment and outcomes. The present study has been conducted in order to evaluate the relation between genetic polymorphism of ALOX5AP gene and developing ischemic stroke in north east of Iran.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in the original study, ALOX5AP mRNA levels were not compared between cases and controls, [ 22 , 25 ] which might also be a limitation of this study. Other limitations are listed as follows.…”
Section: Discussionmentioning
confidence: 98%
“…14 Genome studies have led to identification of many genetic markers of cardiovascular risk/protection in different populations around the world, notably the genes IL1RA, CD14, PON1, ALOX5AP, loci 9p 21.3, and PON1 (Met55Leu and Gln192Arg). [15][16][17][18] Furthermore, studies suggest that the roles played by these cardiovascular risk factors may vary between ethnic groups. [19][20][21][22] These studies indicate that genetic polymorphisms distributed differently in populations of different ethnicities play a fundamental role in the presence of the ethnic/racial differences observed in MS.…”
Section: Introductionmentioning
confidence: 99%